Penerapan Media Bermain Berbasis Learning untuk Meningkatkan Antusiasme Siswa dalam Pembelajaran SPLDV - Zakaria, Allifi Ilma; Hidayah, Shofia; Wibowo, Mahmud Aris (Polinomial : Jurnal Pendidikan Matematika, 2025)
This classroom action research aims to enhance students’ enthusiasm and learning outcomes in mathematics, particularly in the topic of Linear Equations in Two Variables (SPLDV), through the implementation of play-based learning media. The research was conducted collaboratively with the mathematics teacher of Grade IX at MTs Nurul Jadid during the 2025/2026 academic year. The study was carried out in two cycles, each consisting of four stages: planning, action, observation, and reflection.Data were collected through observation sheets and achievement tests. The results revealed a significant improvement in students’ learning motivation and participation. During the pre-cycle, many students were less active and frequently appeared sleepy during lessons. After the implementation of play-based learning media, the classroom atmosphere became more interactive and engaging. Students actively participated in discussions, demonstrated higher focus, and were eager to complete learning activities.The average score increased from 68.75 in the pre-cycle to 74.1 in cycle I and 82.5 in cycle II, with a mastery level reaching 90% of the students. These findings indicate that play-based learning media can effectively increase students’ enthusiasm and improve their understanding of mathematical concepts. It also creates a more enjoyable and meaningful learning experience. Therefore, play-based learning media can serve as an alternative innovative strategy for mathematics teachers to foster active and motivated learning environments.